2023
DOI: 10.3390/w15132320
|View full text |Cite
|
Sign up to set email alerts
|

Physics-Informed Neural Networks-Based Salinity Modeling in the Sacramento–San Joaquin Delta of California

Abstract: Salinity in estuarine environments has been traditionally simulated using process-based models. More recently, data-driven models including artificial neural networks (ANNs) have been developed for simulating salinity. Compared to process-based models, ANNs yield faster salinity simulations with comparable accuracy. However, ANNs are often purely data-driven and not constrained by physical laws, making it difficult to interpret the causality between input and output data. Physics-informed neural networks (PINN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…Just in the past few months, scholars have extensively attempted to use PINN to solve PDE in their own industry field. Roh et al (2023) have attempted to use PINN to solve PDE in salinity transfer kinetics, and have demonstrated that this method has lower absolute deviation than ordinary artificial neural network (ANN) [61]; Singh et al (2023) have integrated particle models into the training process of NN, and have used PINN to predict the charging state and health state of lithium-ion batteries for PDE [62]; Zhou et al ( 2023) have even combined PINN with traditional FEM and have proposed an integrated smooth finite element method (SFEM) to solve elastic-plastic forward and inverse PDEs, which have achieved lower error [63].…”
Section: Solving Pdes Based On Pinnmentioning
confidence: 99%
“…Just in the past few months, scholars have extensively attempted to use PINN to solve PDE in their own industry field. Roh et al (2023) have attempted to use PINN to solve PDE in salinity transfer kinetics, and have demonstrated that this method has lower absolute deviation than ordinary artificial neural network (ANN) [61]; Singh et al (2023) have integrated particle models into the training process of NN, and have used PINN to predict the charging state and health state of lithium-ion batteries for PDE [62]; Zhou et al ( 2023) have even combined PINN with traditional FEM and have proposed an integrated smooth finite element method (SFEM) to solve elastic-plastic forward and inverse PDEs, which have achieved lower error [63].…”
Section: Solving Pdes Based On Pinnmentioning
confidence: 99%
“…Another way is to combine physical knowledge (e.g., salinity transport equations in process-based models) into machine learning models. The combined models are often called physics-informed neural networks (PINN [55][56][57]). In an ongoing study, we are developing PINNs to model salinity at a smaller group of study locations and comparing their performance against that of conventional neural networks.…”
Section: Future Workmentioning
confidence: 99%